Nonisothermal crystallization kinetics in isotactic polypropylene/microcrystalline cellulose (II) composites. Issue 4 (17th May 2016) - Xu, Ning; Xue, Feng; Ding, Enyong
Abstract : This study investigates the polymorphous transformation of microcrystalline cellulose at different NaOH concentrations and the nonisothermal crystallization kinetics of polypropylene/microcrystalline cellulose (II) composites by differential scanning calorimetric technique (DSC) with various cooling rates. The synchrotron X‐ray diffraction reveals that the polymorphous transition from cellulose (I) to cellulose (II) begins at NaOH concentration of 10 (wt%) and the complete transformation is obtained at the NaOH concentration of 15–20 (wt%) during the mercerization process. The Avrami equation was applied to depict the nonisothermal crystallization process and to analyze the experimental data of the composites. The DSC results show that the values of t 1/2 for iPP/MCC (II) composites are lower than that for pure iPP. The polarized optical microscopy images reveal that the peculiar hybrid shish–calabash structure (HSC) with MCC (II) fibers serving as shish and iPP spherulites as calabash finally be formed. POLYM. COMPOS., 39:1064–1075, 2018. © 2016 Society of Plastics Engineers